#1**+1 **

whats 2 over 3 divided by negetive 3 over 4

\(\frac{2}{3}:\frac{-3}{4}=-\frac{2}{3}\times\frac{4}{3}\color{blue}=-\frac{8}{9}\)

!

asinus Aug 23, 2017

#2**0 **

I believe you want to evaluate the expression \(\frac{\frac{\frac{2}{3}}{-3}}{4}\).

When expressions are difficult to evaluate, I like to set the value to a number (I will use *x*)

\(x=\frac{\left(\frac{\left(\frac{2}{3}\right)}{-3}\right)}{4}\) | Multiply by 4 on both sides of the equation. |

\(4x=\frac{\left(\frac{2}{3}\right)}{-3}\) | Multiply by -3 on both sides on both sides. |

\(-12x=\frac{2}{3}\) | Multiply by 3 on both sides. |

\(-36x=2\) | Divide by -36 on both sides to isolate x |

\(x=-\frac{2}{36}=-\frac{1}{18}=-0.0\overline{55}\) | |

I like doing this because it can sometimes make a seemingly hard problem easier. However, you do not have to do this. You can use your knowledge of fractions and its respective rules to solve this expression, too.

\(\frac{\left(\frac{\left(\frac{2}{3}\right)}{-3}\right)}{4}\) | First, let's simply just worry about (2/3)/(-3) |

\(\frac{\frac{2}{3}}{-3}\) | Use the fraction rule that \(\frac{\frac{a}{b}}{c}=\frac{a}{b*c}\) |

\(\frac{2}{3*-3}=\frac{2}{-9}\) | Now, insert this into the equation for (2/3)/(-3) |

\(\frac{\frac{2}{-9}}{4}\) | Let's apply the same fraction rule as before. |

\(\frac{\frac{2}{-9}}{4}=\frac{2}{-9*4}=\frac{2}{-36}\) | Simplify the fraction by noting that both the numerator and denominator are even, so the GCF is, at least, 2. |

\(-\frac{2}{36}=-\frac{1}{18}=-0.0\overline{55}\) | |

TheXSquaredFactor Aug 23, 2017